Impact of Antenna Position and Radiation Patterns on Target Detection in a Highway Environment Utilizing ICAS Extended Model - Khan, Aamir Ullah; Chaudhury, Nandan Dutta; Shah, Syed Najaf Haider; Schneider, Christian; Robert, Joerg (IEEE Vehicular Networking Conference, VNC, 2024)
In this paper, we explore the impact of different antenna positions and radiation patterns on the channel per-formance of an Integrated Communication and Sensing (ICAS) extended model in a highway environment. We have considered a 3-dB omnidirectional Transmitter (Tx) and a directive Receiver (Rx) for our analysis. The antenna radiation patterns of patch and horn antennas are used for the directive receiver. In our system, we have considered three different setups. In the first setup, Rx has a directive antenna (either horn or patch) installed on the car's front bumper. In the second setup, the directive antenna is installed on the car's back bumper. For the third setup, the radiation patterns for the front and back bumper of the car are combined, thus giving rise to Combined Gain Pattern (CGP). The channel responses for the front and back bumper-placed antenna setups are evaluated and compared with the respective CGP setup channel response. The performance of an I CAS system depends on the successful detection of targets. We have considered two types of scatterers in our system. The moving vehicles on the road represent Dynamic Targets (DT) whereas, stationary point reflection sources along the sides of the highway represent Diffuse (DI) scattering components. We have shown in our results that the CGP setup outperforms the front and back bumper-located antenna setups in terms of channel magnitude and accurate target detection capabilities. Moreover, CGP setup helps in modeling the environment better as compared to front and back-bumper installed setups. The horn antenna setup results in superior performance in contrast to the patch antenna setup due to its high directivity.
CRIS-Team Scopus Importer:2024-11-19
Keywords: antenna placement; antenna radiation pattern; ICAS; Selection combining; target detection